The effect of hip manipulation on muscle strength, proprioception and motor tests of basketball players during training - Studnicki, Rafał; Patrzykąt, Zuzanna; Kawczyński, Adam (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study aimed to (i) investigate the effects of diagonal manual therapy on gluteus medius activation and (ii) examine its impact on quadriceps femoris activation, both critical for lower limb stability.MethodsNine male basketball players (mean age 23.8 ± 4.1 years) participated in a randomized crossover trial, with measurements taken before the intervention, immediately after, and following a training session. Muscle activation of the gluteus medius, tensor fascia lata, and quadriceps was assessed via EMG, alongside evaluations of proprioception, the Y-Balance Test, and Standing Broad Jump. Repeated-measures ANOVA revealed significant time effects for all Y-Balance Test directions (anterior, posteromedial, and posterolateral) with large effect sizes (partial η2 > 0.70).ResultsA significant interaction between intervention and assessment was also observed for proprioception at 90° hip flexion (p = 0.073), with a very large effect size (partial η2= 0.835). Main effects of the intervention were significant for maximal and mean activation of the gluteus medius, maximal activation of the tensor fascia lata, and maximal and mean activation of the vastus medialis, with the vastus lateralis showing especially notable maximal activation (partial η2 > 0.65). Furthermore, significant interactions with very large effect sizes (partial η2 often > 0.80) emerged for maximal activation of the gluteus medius, vastus lateralis (maximal, mean, and median values), rectus femoris maximal activation, and vastus medialis mean activation.DiscussionThese findings provide preliminary evidence that diagonal manual therapy effectively enhances neuromuscular activation of the gluteus medius, a key muscle for lower limb stability. Moreover, the intervention influenced activation of other critical muscles such as the vastus lateralis and quadriceps femoris, suggesting a broader neuromuscular facilitation that may benefit dynamic postural control. Improvements in dynamic balance and proprioception further indicate potential functional gains.